2009
DOI: 10.1667/rr1424.1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Targeting of a Catalase Transgene Product by Plasmid Liposomes Increases RadioresistanceIn VitroandIn Vivo

Abstract: To determine whether increased mitochondrially localized catalase was radioprotective, a human catalase transgene was cloned into a small pSVZeo plasmid and localized to the mitochondria of 32D cl 3 cells by adding the mitochondrial localization sequence of MnSOD (mt-catalase). The cell lines 32D-Cat and 32D-mt-Cat had increased catalase biochemical activity as confirmed by Western blot analysis compared to the 32D cl 3 parent cells. The MnSOD-overexpressing 32D cl 3 cell line, 2C6, had decreased baseline cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 29 publications
1
51
0
Order By: Relevance
“…Along with our in vitro data (346) on cytoxic effects of MnPs through H 2 O 2 production when combined with ascorbate, several other groups reported that overexpression of MnSOD kills tumors through H 2 O 2 production (101,130,152,190). We hope that future studies will provide deeper insight into anti-vs. prooxidative actions of compounds (endogenous or exogenous) that are presently primarily considered antioxidants.…”
Section: Cancersupporting
confidence: 72%
See 1 more Smart Citation
“…Along with our in vitro data (346) on cytoxic effects of MnPs through H 2 O 2 production when combined with ascorbate, several other groups reported that overexpression of MnSOD kills tumors through H 2 O 2 production (101,130,152,190). We hope that future studies will provide deeper insight into anti-vs. prooxidative actions of compounds (endogenous or exogenous) that are presently primarily considered antioxidants.…”
Section: Cancersupporting
confidence: 72%
“…A mechanism whereby H 2 O 2 was produced suggested a prooxidative mode of anticancer action of MnPs in the presence of cellular reductants (346). A prooxidative mode of action has been proposed to explain the anticancer effects of the MnSOD enzyme itself by several groups (101,190). A prooxidative action of metalloporphyrins was also reported by others (161,234,253).…”
Section: Reactivity Towardmentioning
confidence: 99%
“…Suppressing this RIP1-mediated catalase expression pathway may sensitize chemotherapy. Indeed, ectopic catalase expression increases radioresistance in vitro and in vivo (34), and targeting tumor cell-protective catalase has been proposed for anticancer therapy (35).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study revealed that overexpression of CAT increased radioresistance (Epperly et al, 2009). In addition, BNC1 is known to be involved in cell proliferation of keratinocytes (Tseng and Green, 1994), but the function of this gene has not yet been clearly defined.…”
Section: Validation Of Cpg Methylation and Mrna Expressionmentioning
confidence: 99%
“…Antioxidants such as CAT, superoxide dismutase, glutathione peroxidase and glutathione reductase were activated on exposure to ionizing radiation. Upregulation of antioxidant proteins led to radioresistance (Epperly et al, 2009) and resistance to the antitumor agent cisplatin (Wang et al, 2008). Hypomethylation of the CAT gene at exon 2 was detected in colon tumor specimens (Ribieras et al, 1994).…”
Section: Global Analysis Of Cpg Methylation For Radiosensitivitymentioning
confidence: 99%